ADENOMYOSIS AND PREGNANCY OUTCOMES: PROGNOSIS AND PREVENTION OF OBSTETRICS COMPLICATIONS - Akhmedjanova Khurshidakhan Zakirjan kizi (Journal Park Publishing, 2025)
This article discusses the impact of adenomyosis on the course of pregnancy and the risk of perinatal complications, such as premature birth, fetal hypoxia, intrauterine growth retardation, and placental insufficiency. Adenomyosis is a disease characterized by the proliferation of the endometrium into the muscular layer of the uterus, which can lead to changes in its structure and functionality, especially during pregnancy. The aim of the study is to study prognostic factors that allow early detection of the risks of complications in women with adenomyosis. The article also discusses modern methods of prevention aimed at minimizing adverse perinatal outcomes and provides recommendations for pregnancy management in the presence of adenomyosis, taking into account the individual characteristics of patients and the use of the latest therapeutic approaches.
Keywords: Adenomyosis, perinatal complications, pregnancy, prognosis, prevention, premature birth, fetal hypoxia, placental insufficiency, intrauterine development.